2013
DOI: 10.1080/13854046.2013.835447
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Effort: Differentiating Performance and Symptom Validity

Abstract: The current study aimed to clarify the relationship among the constructs involved in neuropsychological assessment, including cognitive performance, symptom self-report, performance validity, and symptom validity. Participants consisted of 120 consecutively evaluated individuals from a veteran's hospital with mixed referral sources. Measures included the Wechsler Adult Intelligence Scale-Fourth Edition Full Scale IQ (WAIS-IV FSIQ), California Verbal Learning Test-Second Edition (CVLT-II), Trail Making Test Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 24 publications
4
48
1
1
Order By: Relevance
“…However, there was not complete overlap between Veterans who scored above the cutoff on the Validity-10 and those who failed the PVT variable, which supports the use of both PVTs and SVTs when determining validity of assessment in this population because SVT failure and PVT failure are not completely overlapping constructs [21,36].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, there was not complete overlap between Veterans who scored above the cutoff on the Validity-10 and those who failed the PVT variable, which supports the use of both PVTs and SVTs when determining validity of assessment in this population because SVT failure and PVT failure are not completely overlapping constructs [21,36].…”
Section: Discussionmentioning
confidence: 87%
“…VA service connection was also a significant predictor in the model; however, the second model that did not include this variable was also significant. The Validity-10 continued to contribute additional, albeit modest, predictive utility to both models after psychiatric comorbidities and VA service connection were accounted for, providing support for the strong relationship between SVTs and PVTs as well as the incremental predictive utility that accompanies the use of an SVT [36]. This finding is only partially congruent with a study by Armistead-Jehle that found SVT performance was clinically elevated in Veterans with a history of mTBI who failed PVTs but did not significantly predict PVT failure [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this term tends to be used mostly in reference to the latter (often referred to as effort testing). Some researchers have recently distinguished between performance validity tests (PVTs) and reserve the term "SVTs" for symptom reporting validity measures (Larrabee, 2012;Van Dyke, Millis, Axelrod, & Hanks, 2013). For the purposes of this review, the term "PVT" is used synonymously with effort testing.…”
mentioning
confidence: 99%
“…Since the early nineties, there has been a steady increase in empirical and meta-analytic studies evaluating the diagnostic accuracy of tools designed to identify distorted symptom presentation (e.g., Sweet & Guidotti Breting, 2013). In keeping with the terminology of other authors (Larrabee, 2012;Van Dyke, Millis, Axelrod, & Hanks, 2013), we use response validity tests as an overarching term for these tools. Broadly speaking, there are two types of response validity tests: (a) self-report symptom validity tests (SVTs) that intend to measure overreporting of symptoms, and (b) performance validity tests (PVTs) that assay underperformance on cognitive tests (Greve, Bianchini, & Brewer, 2013).…”
mentioning
confidence: 99%